2015
DOI: 10.1113/ep085361
|View full text |Cite
|
Sign up to set email alerts
|

Responses of sex steroid hormones to different intensities of exercise in endurance athletes

Abstract: New Findings r What is the central question of this study?What is the effect of different exercise intensities on sex steroid hormone concentrations in individuals with different degrees of physical fitness? r What is the main finding and its importance?In endurance athletes, serum concentrations of sex steroid hormones increased only with high-intensity exercise. Moreover, different responses of sex steroid hormone secretions were induced by different exercise intensities in individuals with low and high leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 28 publications
2
37
0
Order By: Relevance
“…Men also show an inverse relationship between reproductive investment and physical activity. As with inflammation and HPA activity, testosterone levels rise during exercise, but endurance athletes exhibit lower baseline levels and a blunted exercise-induced rise (29,31,72). Morning salivary testosterone is also lower among men in physically active non-industrial populations compared with those in less active, industrialized countries (21).…”
Section: Reproductive Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Men also show an inverse relationship between reproductive investment and physical activity. As with inflammation and HPA activity, testosterone levels rise during exercise, but endurance athletes exhibit lower baseline levels and a blunted exercise-induced rise (29,31,72). Morning salivary testosterone is also lower among men in physically active non-industrial populations compared with those in less active, industrialized countries (21).…”
Section: Reproductive Functionmentioning
confidence: 99%
“…The suppressive effects of exercise are often attributed to "energy stress" or inadequate intake (24,27,35,49,72,76). But with the superabundance of food energy in modern industrialized populations, it is unclear why increased physical activity should result in energy stress, unless TEE is constrained.…”
Section: Constrained Tee and The Health Effects Of Exercisementioning
confidence: 99%
“…Several studies have reported that acute aerobic exercise increases circulating testosterone levels in men [20][21][22][23][24]. Therefore, it is possible that regular aerobic exercise increases circulating testosterone levels.…”
Section: Introductionmentioning
confidence: 99%
“…Further evidence that acute exercise may modify the assumed gonadosteroid conversion pathway (i.e. DHEA‒androstenedione‒testosterone‒5α‐dihydrotestosterone) was observed by Sato and colleagues (). In their study, low‐intensity endurance exercise increased DHEA and free testosterone concentrations in untrained subjects, but 5α‐dihydrotestosterone increased only during high‐intensity endurance exercise.…”
Section: Discussionmentioning
confidence: 77%